Noisy Information, Interest Rate Shocks and the Great Moderation - Johann Scharler; Eric Mayer (Verein für Socialpolitik, 2010)
In this paper we quantitatively evaluate the hypothesis that the Great Moderation is partly the result of a less activist monetary policy. We simulate a New Keynesian model where the central bank can only observe a noisy estimate of the output gap and find that the less pronounced reaction of the Federal Reserve to output gap fluctuations since 1979 can account for half of the reduction in the standard deviation of GDP associated with the Great Moderation. Our simulations are consistent with the empirically documented smaller magnitude and impact of interest rate shocks since the early 1980s.
Keywords: E32; E52; E58; 330; Great Moderation; New Keynesian Model; Noisy Data